Diversity and organizational development : impacts and opportunities - Kuklenski, Jennifer (Emerald Publishing Limited, 2021)
As modern societies become more diverse and multicultural, the call for greater inclusion within organizations is getting louder. In response, many organizations have rushed to diversify, without fully understanding the implicit and explicit levels of diversity, the complexity of social identities, and the hidden and often unintended ways differences between members of in-groups and out-groups can lead to social exclusion. By providing a thorough overview of the concept of diversity, distinguishing between competing definitions and types of cultural and cognitive differences, Diversity and Organizational Development helps current and future leaders develop their diversity competency. Concepts of diversity management are explained as value-added activities that increase creativity and innovation, improve problem-solving and organizational flexibility, and aid in the recruitment and retention of top talent. Drawing upon interdisciplinary perspectives from business, economics, psychology, and sociology, this work offers a comprehensive approach to inclusive organizational development through which diversity and inclusion initiatives are supported by all facets of organizational operations and culture. Readers are shown how organizations can move toward the integrating stage of organizational development, during which members of all cultural and identity groups feel included, valued, and empowered through their contributions to organizational success. Making a case for inclusive development through organizational culture, this book further demonstrates how rituals, symbols, and language can create shared meaning among members of diverse organizations, powerfully influencing their effectiveness and strategic performance, while ultimately creating more satisfying workplaces.